Dimensi Motivasi Belajar: Telaah Komparatif Antara Islam dan Psikologi - Sandy Aulia Rahman (PT. Ahlal Publisher Nusantara, 2025)
Learning motivation is one of the main factors that determine the success of the educational process. Motivation not only encourages individuals to be active and consistent in learning, but also plays a role in forming meaningful learning goals. This study uses a library research method to analyze learning motivation through Islamic and psychological perspectives. The results of the study indicate that learning motivation from a psychological perspective is influenced by various factors, such as basic needs according to Maslow's Hierarchy of Needs Theory, internal and external motivation according to Herzberg's Two Factor Theory, and the influence of expectations and achievement needs as explained in Vroom's Expectancy Theory and McClelland's Achievement Motive. In addition, Islam offers a unique perspective by emphasizing the integration between psychological and spiritual aspects, where the concept of reward and sin acts as a driver to do good deeds. This study concludes that an integrative approach between psychological theory and Islamic values can enrich the understanding of learning motivation. Learning motivation is not only oriented towards worldly achievements, but also towards achieving the goals of the afterlife, thus providing guidance for achieving a balance between material and spiritual needs in the learning process.